Oxford Handbook of Clinical Examination and Practical Skills, 1st Edition - Thomas, James , Monaghan, Tanya (OXFORD UNIVERSITY PRESS, 2007)
There are very few people who, in the course of their daily work, can approach a stranger, ask them to remove their clothes, and touch their bodies without fear of admonition. This unique position of doctors, medical students, and other health care professionals comes with many strings attached. We are expected to act Ã¢â‚¬ËœprofessionallyÃ¢â‚¬â„¢ and be competent and confident in all our dealings. This is hard to teach and hard to learn and many students are rightly daunted by the new position in which they find themselves. We felt a little let down by many books during our time in medical school, and often found ourselves having to dip into several texts to appreciate a topic. This book, then, is the one text that we would have wanted as students covering all the main medical and surgical subspecialties. We anticipate it will be useful to students as they make the transition to being a doctor and also to junior doctors. We hope that it will be carried in coat pockets for quick glances as well as being suitable for study at home or in the library. The first three chapters cover the basics of communication skills, history taking and general physical examination. Chapters 4,5,6,7,8,9,10,11,12,13 and 14 are divided by systems. In each of these there is a section on the common symptoms seen in that system, with the appropriate questions to ask the patient, details of how to examine parts of that system, and important patterns of disease presentation. Each of these system chapters is finished off with an Ã¢â‚¬Ëœelderly patientÃ¢â‚¬â„¢ page provided by Dr Richard Fuller. Following the systems, there are chapters on paediatric and psychiatric patientsÃ¢â‚¬â€something not found in many other books of this kind. The penultimate chapterÃ¢â‚¬â€practical proceduresÃ¢â‚¬â€details all those tasks that junior doctors might be expected to perform. Finally, there is an extensive Ã¢â‚¬Ëœdata interpretationÃ¢â‚¬â„¢ chapter which, whilst not exhaustive, tries to cover those topics such as ECG, ABG, and X-ray interpretation that may appear in a final Ã¢â‚¬ËœOSCEÃ¢â‚¬â„¢ examination. Although we have consulted experts on the contents of each chapter, any mistakes or omissions remain ours alone. We welcome any comments and suggestions for improvement from our readerÃ¢â‚¬â€this book, after all, is for you.